Public Space Contestation and the Limits of Bureaucratic Effectiveness: The Law Enforcement Dilemma and Street Vendor Resilience in Jalan Veteran, Malang - Agustinus Ghunu; Dody Setyawan; Santi Lingga Luda (Universitas Tribhuwana Tungga Dewi, 2026)
This study aims to analyze the implementation of the street vendor control policy based on Malang City Regional Regulation Number 2 of 2012 concerning Public Order and Environment in the Jalan Veteran area, as well as to identify supporting factors, inhibiting factors, and its impact on public order. The research problem centers on the persistent use of sidewalks and road shoulders by street vendors despite repeated enforcement actions. Utilizing a descriptive qualitative approach, data were collected through observation, documentation, and in-depth interviews with Satpol PP officers, Department of Trade officials, street vendors, and road users. Data were analyzed using George C. Edward III’s policy implementation framework, which encompasses four variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that policy implementation has not yet operated optimally. In terms of communication, policy dissemination remains uneven, resulting in limited understanding among vendors. Regarding resources, implementation is constrained by personnel shortages and a lack of relocation space. On disposition, enforcement officers demonstrate good commitment, yet rule enforcement consistency fluctuates. Meanwhile, regarding bureaucratic structure, task allocation details are clear, but inter-agency coordination lacks optimal synergy. Overall, the policy contributes to improving local public order, but its impact is not yet sustainable, necessitating enhanced educational outreach, cross-sectoral coordination, and the provision of adequate relocation facilities.Penelitian ini bertujuan menganalisis implementasi kebijakan penertiban pedagang kaki lima (PKL) berdasarkan Peraturan Daerah Kota Malang Nomor 2 Tahun 2012 tentang Ketertiban Umum dan Lingkungan di kawasan Jalan Veteran, serta mengidentifikasi faktor pendukung, penghambat, dan dampaknya terhadap ketertiban umum. Permasalahan penelitian berpusat pada maraknya penggunaan trotoar dan bahu jalan oleh PKL yang persisten meskipun tindakan penertiban telah berulang kali dilakukan. Dengan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi, dokumentasi, serta wawancara mendalam bersama aparatur Satpol PP, Dinas Perdagangan, PKL, dan pengguna jalan. Data dianalisis menggunakan kerangka model implementasi George C. Edward III yang mencakup komunikasi, sumber daya, disposisi, dan struktur birokrasi. Hasil penelitian menunjukkan bahwa implementasi kebijakan belum berjalan secara optimal. Dari aspek komunikasi, sosialisasi kebijakan belum merata sehingga pemahaman pedagang terbatas. Pada aspek sumber daya, pelaksanaan terkendala oleh keterbatasan personel dan minimnya lahan relokasi. Pada aspek disposisi, komitmen aparat tergolong baik namun konsistensi penegakan aturan masih berfluktuasi. Sementara pada aspek struktur birokrasi, rincian pembagian tugas sudah jelas tetapi koordinasi lintas instansi belum bersinergi maksimal. Secara umum, kebijakan ini berkontribusi terhadap perbaikan ketertiban kawasan, namun dampaknya belum berkelanjutan sehingga memerlukan penguatan sosialisasi edukatif, koordinasi lintas sektor, serta penyediaan fasilitas relokasi yang memadai.